Combined effects of temperature and clomazone (Gamit®) on oxidative stress responses and B-esterase activity of Physalaemus nattereri (Leiuperidae) and Rhinella schneideri (Bufonidae) tadpoles. (October 2017) - Freitas, Juliane Silberschmidt; Felício, Andreia Arantes; Teresa, Fabrício Barreto; Alves de Almeida, Eduardo
Abstract: Temperature is an important factor influencing the toxicity of chemicals in aquatic environments. Neotropical tadpoles experience large temperature fluctuations in their habitats and many species are distributed in areas impacted by agriculture. This study evaluated the effects caused by the exposure to clomazone (Gamit ® ) at different temperatures (28, 32 and 36 °C) on biochemical stress responses and esterase activities in Physalaemus nattereri and Rhinella schneideri tadpoles. Results evidenced that temperature modulates the effects of clomazone on biochemical response of tadpoles. Antioxidant enzymes, including catalase, superoxide dismutase (SOD), and glucose- 6 -phosphate dehydrogenase had their activities increased by clomazone in P. nattereri treated at higher temperatures. The biotransformation enzyme glutathione- S -transferase (GST) was also induced by clomazone at 32 and 36 °C. In R. schneideri, clomazone failed to alter antioxidant enzymes at 28 °C, but SOD and GST were increased by clomazone at higher temperatures after three days. All enzymes had their activities returned to the control levels after eight days in R. schneideri. Lipid peroxidation was induced in both species exposed to clomazone at 32 and 36 °C, but not at 28 °C. Acetylcholinesterase was not sensitive to clomazone and temperature, while most treatments impaired carboxylesterase activity. Integrated biomarker response (IBR) was notably induced by temperature in both species, and a synergic effect of temperature and clomazone was mostly observed after three days of exposure. These findings imply that tadpoles from tropical areas may present differential responses in their physiological mechanism linked to antioxidant defense to deal with temperature fluctuations and agrochemicals presence in their habitats. Graphical abstract: Highlights: Clomazone effects at 28, 32 and 36 °C were evaluated in two tadpole species. Temperature enhanced oxidative stress in tadpoles exposed to clomazone. Carboxilesterase, but not acetylcholinesterase, was altered by clomazone. Neotropical tadpoles have different vulnerability to the heat stress and chemicals. Temperature effect was more evident than clomazone effects by the IBR analysis.